2017
DOI: 10.1111/pde.13190
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Herpes Simplex Virus Infections Seen in the Pediatric Dermatology Office

Abstract: Our data characterize a subset of immunocompetent young children who present to pediatric dermatologists with frequent HSV outbreaks that are often multifocal and involve cutaneous sites, with or without mucosal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
0
2
Order By: Relevance
“…Only one study by Gittler et al reported characteristics of children ( n = 48) with recurrent HSV infections: 39.6% had more than 6 outbreaks per year, and suppressive therapy was initiated in 33.3% cases at mean age of 6 years, but no data on efficacy or type of treatment were provided 3 . The main locations were herpes labialis and herpetic whitlow in our study, and these characteristics were not described in the study by Gittler.…”
Section: Characteristics Number Of Available Data N (%)contrasting
confidence: 55%
See 1 more Smart Citation
“…Only one study by Gittler et al reported characteristics of children ( n = 48) with recurrent HSV infections: 39.6% had more than 6 outbreaks per year, and suppressive therapy was initiated in 33.3% cases at mean age of 6 years, but no data on efficacy or type of treatment were provided 3 . The main locations were herpes labialis and herpetic whitlow in our study, and these characteristics were not described in the study by Gittler.…”
Section: Characteristics Number Of Available Data N (%)contrasting
confidence: 55%
“…(n = 48) with recurrent HSV infections: 39.6% had more than 6 outbreaks per year, and suppressive therapy was initiated in 33.3% cases at mean age of 6 years, but no data on efficacy or type of treatment were provided. 3 The main locations were herpes labialis and herpetic whitlow in our study, and these characteristics were not described in the study by Gittler. Herpetic whitlows are a clinical presentation important to know for physicians, as they are often misdiagnosed as a bacterial infection, as described by Szinnai et al who showed that only 23% of the herpetic whitlow were correctly diagnosed.…”
Section: Only One Study By Gittler Et Al Reported Characteristics Of ...contrasting
confidence: 51%